Progression of Bone Marrow Lesions and the Development of Knee Osteoarthritis: Osteoarthritis Initiative Data - Moradi, Kamyar; Mohammadi, Soheil; Roemer, Frank W.; Momtazmanesh, Sara; Hathaway, Quincy; Ibad, Hamza Ahmed; Hunter, David J.; Guermazi, Ali; Demehri, Shadpour (Radiology, 2024)
Background: Bone marrow lesions (BMLs) are a known risk factor for incident knee osteoarthritis (OA), and deep learning (DL) methods can assist in automated segmentation and risk prediction. Purpose: To develop and validate a DL model for quantifying tibiofemoral BML volume on MRI scans in knees without radiographic OA and to assess the association between longitudinal BML changes and incident knee OA. Materials and Methods: This retrospective study included knee MRI scans from the Osteoarthritis Initiative prospective cohort (February 2004-October 2015). The DL model, developed between August and October 2023, segmented the tibiofemoral joint into 10 subregions and measured BML volume in each subregion. Baseline and 4-year follow-up MRI scans were analyzed. Knees without OA at baseline were categorized into three groups based on 4-year BML volume changes: BML-free, BML regression, and BML progression. The risk of developing radiographic and symptomatic OA over 9 years was compared among these groups. Results: Included were 3869 non-OA knees in 2430 participants (mean age, 59.5 years ± 9.0 [SD]; female-to-male ratio, 1.3:1). At 4-year follow-up, 2216 knees remained BML-free, 1106 showed an increase in BML volume, and 547 showed a decrease in BML volume. BML progression was associated with a higher risk of developing radiographic knee OA compared with remaining BML-free (hazard ratio [HR] = 3.0; P < .001) or BML regression (HR = 2.0; P < .001). Knees with BML progression also had a higher risk of developing symptomatic OA compared with BML-free knees (HR = 1.3; P < .001). Larger volume changes in BML progression were associated with a higher risk of developing both radiographic OA (HR = 2.0; P < .001) and symptomatic OA (HR = 1.7; P < .001). In almost all subchondral plates, especially the medial femur and tibia, BML progression was associated with a higher risk of developing both radiographic and symptomatic OA compared with remaining BML-free. Conclusion: Knees with BML progression, according to subregion and extent of volume changes, were associated with an increased risk of OA compared with BML-free knees and knees with BML regression, highlighting the potential utility of monitoring BML volume changes in evaluating interventions to prevent OA development.
CRIS-Team Scopus Importer:2024-09-27